(untitled) (Research, Society and Development, 2019)
The study aims to understand the relationship between maternity and the labor market from the perspective of a working mother. Thus, a qualitative questionnaire was used through an instant messaging application with a trainee from a federal educational institution that is the mother of three children and has her daily work routine reconciled with the care of the children. This study revealed that returning to work with young children who depended on it was one of the main difficulties, citing as the main problem that they were not being as well cared for and educated as they would care for or educate. It was quoted as interferences of the children have already needed to miss work because they get sick or need to go to the doctor, in these cases the bosses accept, but do not like. Therefore, the study points out that the relationship between motherhood and the labor market from the perspective of a working mother is, despite difficulties, possible, however, requires a dialogue between the worker and the institution and the understanding of the organization.